THE RELATIONSHIP OF DAILY LIVING ACTIVITY (ADL) WITH ANXIETY LEVEL IN THE ELDERLY AT SOCIAL SERVICE UPT DEAF, SPEECH AND ELDERLY SOCIAL SERVICES PEMATANG SIANTAR - Federik Marpaung, Ricard; Hotria Siregar, Pinondang (CV. Radja Publika, 2022)
Activity Daily Living (ADL) is a basic skill that a person must have in taking care of himself, including clothing, eating, drinking, toileting, bathing and making up. The elderly will experience a decrease in carrying out daily activities and can directly cause harm to the elderly. Elderly is someone who has entered the age of 60 years and over. This study aims to see the relationship of daily activities (ADL) with the level of the elderly at the Social Service Unit for the Deaf, Speech and Elderly, Pematangsiantar social service. This type of research is descriptive correlation through cross sectional approach. This research was conducted from September to October 2020. The population in this study were the elderly at the Social Service Unit for the Deaf, Speech and Elderly at the Pematangsiantar Social Service as many as 30 people. Sampling in this study is using total sampling, which means that all members of the population can be sampled, namely 30 people. The results of this study were that data processing using SPSS, in an indigo P = 0.03 (P <0.05), so that Ho was rejected, meaning that this study had a statistically close relationship between activities of daily life (ADL) and the level of reduction in elderly and elderly at the Social Service Unit for the Deaf, Speech and Elderly, Pematangsiantar Social Service.